2017
DOI: 10.1016/j.cplett.2017.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Various complexity measures in confined hydrogen atom

Abstract: Several well-known statistical measures similar to LMC and Fisher-Shannon complexity have been computed for confined hydrogen atom in both position (r) and momentum (p) spaces. Further, a more generalized form of these quantities with Rényi entropy (R) is explored here. The role of scaling parameter in the exponential part is also pursued. R is evaluated taking order of entropic moments α, β as ( 2 3 , 3) in r and p spaces. Detailed systematic results of these measures with respect to variation of confinement … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 37 publications
0
17
0
1
Order By: Relevance
“…This is because they satisfy a number of mathematical requirements as already pointed out. However, other proposals of complexity‐like measures that do not generally satisfy the full set of criteria of an intrinsic statistical complexity show a similar behavior for all states, not being able to fully capture the internal structure of the system.…”
Section: Complexity Measuresmentioning
confidence: 97%
“…This is because they satisfy a number of mathematical requirements as already pointed out. However, other proposals of complexity‐like measures that do not generally satisfy the full set of criteria of an intrinsic statistical complexity show a similar behavior for all states, not being able to fully capture the internal structure of the system.…”
Section: Complexity Measuresmentioning
confidence: 97%
“…However, in confined environment LMC complexity has been investigated only for ground state of some model systems, like, CHO, confined h-atom, particle in spherical box and confined Helium atom [36,37]. Very recently, the present authors have pursued similar calculations for confined hydrogen atom [38] and found that, parameter b plays a key role in interpreting the property of a system. In this endeavor, our objective is to explore four different types of complexity emerging out of two order (I, E) and two disorder (S, R) parameters, in conjugate spaces, as functions of confinement radius (r c ).…”
Section: Introductionmentioning
confidence: 96%
“…This sum has been applied, along with other information measures, to study confined quantum systems . Confined quantum systems are of interest since they can be used to model systems at extreme pressures, including astrophysical and nanotechnological ones .…”
Section: Introductionmentioning
confidence: 99%